2013
DOI: 10.1002/hep.26321
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of intestinal mucin-2 ameliorates experimental alcoholic liver disease in mice

Abstract: The intestinal mucus layer protects the epithelium from noxious agents, viruses, and pathogenic bacteria present in the gastrointestinal tract. It is composed of mucins, predominantly mucin-2 (Muc2), secreted by goblet cells of the intestine. Experimental alcoholic liver disease requires translocation of bacterial products across the intestinal barrier into the systemic circulation, which induces an inflammatory response in the liver and contributes to steatohepatitis. We investigated the roles of the intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
205
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 205 publications
(224 citation statements)
references
References 46 publications
8
205
0
3
Order By: Relevance
“…Presently, the identity of the endogenous lipid antigens that contribute to chronic-plus-binge ethanol-induced hepatic iNKT cell activation is unknown. It is known that chronic ethanol feeding induces gut bacterial overgrowth and increases gut permeability, [29][30][31] which may result in elevated hepatic levels of bacterial products, such as glycosphingolipids, which can induce CD1d-dependent NKT cell activation. 32 Interestingly, a recent study reported that incubation with physiological concentrations of ethanol stimulated NKT cell activation by enhancing CD1d glycolipid loading.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the identity of the endogenous lipid antigens that contribute to chronic-plus-binge ethanol-induced hepatic iNKT cell activation is unknown. It is known that chronic ethanol feeding induces gut bacterial overgrowth and increases gut permeability, [29][30][31] which may result in elevated hepatic levels of bacterial products, such as glycosphingolipids, which can induce CD1d-dependent NKT cell activation. 32 Interestingly, a recent study reported that incubation with physiological concentrations of ethanol stimulated NKT cell activation by enhancing CD1d glycolipid loading.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of cirrhosis-related deaths are due to alcohol abuse (2). Chronic alcoholism can lead to intestinal bacterial overgrowth and dysbiosis, a leaky gut barrier, and increased systemic levels of bacterial products (3)(4)(5)(6)(7). Although the intestinal microbiome contains bacteria, fungi, and viruses, research in the field of alcohol-associated disease has almost exclusively focused on the interaction between the host and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are employed to encourage animals to consume a specific amount of substance in a particular timeframe, a motivation that is distinct from those that drive human consumption of alcohol. In other models of alcoholism, animals do not willingly consume alcohol at all, but are rather injected intraperitoneally or subcutaneously, or receive ethanol via gavage or intubation (Girard, Xing, Ward, & Wainwright, 2000;Hartmann et al, 2013;Tran, Cronise, Marino, Jenkins, & Kelly, 2000). Moreover, due to species-specific differences in metabolism and scale, the quantity of alcohol consumed by laboratory animals does not easily translate to realistic quantities consumed by adult humans (Zorzano & Herrera, 1990).…”
Section: Current Status Of Dual Diagnosis Researchmentioning
confidence: 98%